Overcome Anemia in Pregnant Women With Counseling and Giving Beetroot Juice to Prevent Anemia - Febry Mutiariami Dahlan; Sehan, Iis; Intiani Kusuma Dewi; Lina Roslina; Siti Aisyah; Nurmala; Eny Susanti; Fatmawati Karim (Rajaki of Tulip Medika Publisher, 2024)
Anemia in pregnant women is a condition in which the body can’t produce enough red blood cells to circulate oxygen to the body's tissues during pregnancy. Beetroot is one of the non-pharmacological treatments that is very useful for increasing hemoglobin levels. The purpose of community service is to help pregnant women with anemia by increasing hemoglobin levels in pregnant women by giving beetroot juice to pregnant women in the Karyamulya Village area, Batujaya District. This community service was carried out in Karyamulya Village, Batujaya District. The activities of community service go through 3 stages, namely the preparation, implementation, and evaluation stages. The results of the counseling showed that there was a difference in HB levels before and after counseling and intervention in the administration of beetroot juice. Before being given beetroot juice, all respondents 20 (100%) had anemia, while after being given counseling and beetroot juice, most of the respondents did not experience anemia, namely 17 (85%) respondents, and 3 (15%) respondents experienced anemia Counseling and giving beetroot juice for pregnant women with anemia is very effective because it follows health conditions, namely anemia in pregnancy which is experienced by many pregnant women in the region. Anemia in pregnant women is a condition in which the body can’t produce enough red blood cells to circulate oxygen to the body's tissues during pregnancy. Beetroot is one of the non-pharmacological treatments that is very useful for increasing hemoglobin levels. The purpose of community service is to help pregnant women with anemia by increasing hemoglobin levels in pregnant women by giving beetroot juice to pregnant women in the Karyamulya Village area, Batujaya District. This community service was carried out in Karyamulya Village, Batujaya District. The activities of community service go through 3 stages, namely the preparation, implementation, and evaluation stages. The results of the counseling showed that there was a difference in HB levels before and after counseling and intervention in the administration of beetroot juice. Before being given beetroot juice, all respondents 20 (100%) had anemia, while after being given counseling and beetroot juice, most of the respondents did not experience anemia, namely 17 (85%) respondents, and 3 (15%) respondents experienced anemia Counseling and giving beetroot juice for pregnant women with anemia is very effective because it follows health conditions, namely anemia in pregnancy which is experienced by many pregnant women in the region.